Teacher Capacity Building through Curriculum–Student Affairs Integration: The IKRKT Model - Qurroti A’yun; Ilfi Nurdiana; Akhmad Nurul Kawakip (GHAITSA : Islamic Education Journal, 2026)
This article formulates a teacher capacity development model that links individual competence with school organizational performance. The study addresses the tendency of teacher development to remain training-oriented and weakly connected to organizational learning. A qualitative single-case embedded design was employed at SDI Al-Ma’arif 02 Singosari, with curriculum and student affairs as embedded units. Data were collected through interviews, observation, and documents, and analyzed through interactive analysis, within-unit analysis, and cross-unit synthesis. The findings show that capacity development was planned through needs mapping, strategic alignment, governance, curriculum–student affairs integration, and professional learning communities. Implementation involved routine and incidental activities, teacher working groups, supervision, mentoring, workshops, internal-external collaboration, evaluation, reflection, and follow-up. Cross-unit synthesis generated the IKRKT Model, consisting of Integrative, Collaborative, Reflective, Continuous, and Transformative dimensions. The model explains how individual teacher competence can become collective organizational capacity that strengthens educational service quality and school performance.